2018
DOI: 10.1177/2058738418785514
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and camel milk abate oxidative stress status, genotoxicity induced in valproic acid rat model of autism

Abstract: The aspect of treatment of autistic behaviour was investigated using valproic acid rat model of pregnant female rats. Two main groups (10 male rats/group) were treated for 6 days and then divided into six subgroups. The first group of normal rats was divided into three subgroups: (A) – control group, (B) – treated with camel milk (CAM; 2 mL/p.o) and (C) – treated with leptin (1000 µg/kg i.p) twice daily. The second group of autistic rats was randomly distributed into four subgroups as follows: (D) – positive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 55 publications
0
17
1
1
Order By: Relevance
“…Our results also revealed an increase in the apoptotic proteins along with a decrease in the developmentally proteins due to the negative effects of vitrification treatment on rabbit embryos not previously treated with leptin ( Fig 3 ). In contrast, the positive effect of leptin on fresh embryos in the present study could be attributed to the antiapoptotic action of leptin via downregulation of P53 and MAP kinase pathways which consequently reduce genetic expression of apoptotic proteins like Caspase3, TNFα and BAX [ 43 , 60 , 61 ]. Furthermore, culture of embryos with leptin before vitrification ameliorated the reduction in the developmental biomarkers induced by the vitrification in the present study ( Fig 4B ).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Our results also revealed an increase in the apoptotic proteins along with a decrease in the developmentally proteins due to the negative effects of vitrification treatment on rabbit embryos not previously treated with leptin ( Fig 3 ). In contrast, the positive effect of leptin on fresh embryos in the present study could be attributed to the antiapoptotic action of leptin via downregulation of P53 and MAP kinase pathways which consequently reduce genetic expression of apoptotic proteins like Caspase3, TNFα and BAX [ 43 , 60 , 61 ]. Furthermore, culture of embryos with leptin before vitrification ameliorated the reduction in the developmental biomarkers induced by the vitrification in the present study ( Fig 4B ).…”
Section: Discussioncontrasting
confidence: 60%
“…Leptin was previously reported as antioxidant and free radical scavenger in a rat model suffer from oxidative stress [ 43 , 44 ]. There is only one study reported a positive effect of leptin on cryopreserved men sperm which was induced by the activation of certain antioxidant enzymes [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Badr et al (2017) presented similar properties of CM. Hamzawy et al (2018) also observed that CM abate oxidative stress (measured by the level of TBARS and activity of various antioxidant enzymes) in a rat model of autism. In addition, results of Meena et al (2016) have demonstrated that CM ameliorates oxidative damages in type-1 diabetic experimental rats.…”
Section: Lipid Peroxidation Measurement and Thiol Group Determinationmentioning
confidence: 81%
“…These abnormalities occur due to defects in proliferation and differentiation in pancreatic cells during embryonic development [ 7 , 8 ]. Moreover, VPA is associated with the induction of oxidative stress, inflammatory reactions including pancreatitis, and apoptosis [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%